Periodontitis and its relationship with ischemic stroke (Ictus, 2020)
Periodontitis has been linked to ischemic stroke (IS) and has been described as a risk factor for developing IS, however, the evidence on its relationship is controversial. The objective of this review is to describe the epidemiological impact, pathophysiological mechanisms, and clinical relevance of the relationship between periodontal disease and IS. Epidemiological studies show that periodontitis increases the risk of developing IS; effect produced through the systemic pro-inflammatory state as a consequence of periodontitis, favoring the formation of atheromatous plaques in large arteries. Furthermore, the bacterial DNA of periodontitis-causing pathogens has been identified in atheromatous plaques of patients with IS. Recent studies suggest that the Intima Media Thickness (IMT) measured by ultrasound is largely related to cardiovascular risk factors and recently to periodontitis. Finally, treatment of periodontitis has been shown to reduce the risk of IS. The relationship between periodontitis and IS is clear. However, it is necessary to develop randomized studies to measure its relationship more precisely and to implement effective strategies for the detection and timely treatment of periodontitis to reduce the burden of disease represented by stroke.
Keywords: Periodontitis; Ischemic stroke; Atherosclerosis; Pathophysiology; Dental health